Analysis Of the Influence of Work Discipline and Motivation on The Performance of Employees of The Central Statistics Agency (BPS) Of Langkat Regency - Abdul Rahman Effendi; Ahmad Azmi; Akhmad Taufik (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze work discipline and motivation for employee performance at the Central Statistics Agency (BPS) of Langkat Regency. Where there is a bound variable, namely employee performance and there are two independent variables, namely work discipline and work motivation. This study uses primary data by searching for data through the office of the Central Statistics Agency (BPS) of Lalat Regency. The data analysis model in this study uses Multiple Linear Regression. The results of the study showed that the variables of work discipline and work motivation had a significant effect on employee performance at the Central Statistics Agency (BPS) of Langkat Regency.